Estimate reliable function of nonparametric methods in the case of surveillance data accumulated - Bashir Faisal Mohammed (Journal of Madenat Alelem University College, 2014)
This research aims to estimate reliable function of nonparametric methods (Simple Actuarial Method, Standard Actuarial Method and Weighted Kaplan – Meier Method) in the case of surveillance data (accumulated), and analyze the results of the methods to reach the best method of nonparametric through using of disaggregated data real Babylon (1) Laboratory machines of liquid batteries that depending onthe ratio of the standard error of measurement.